THE REPUBLIC OF BULGARIA DEVELOPMENT WITH REGARD TO GEO-FINANCE RISKS: YESTERDAY, TODAY AND TOMORROW - Evgeniy V. Afanasyev; Ivan P. Ivanov (Вестник Российского экономического университета имени Г. В. Плеханова)
On the basis of statistic analysis and comparative characteristic the article describes negative risks and consequences of acute geo-finance policy of the Republic of Bulgaria in 2016. International finance and economic policy and Euro-integration of Bulgaria in conditions of the Currency Board, growing indebtedness with effective membership of the country in the EU and continuous finance dependence on the World Bank, WMF and ECB provide an opportunity to trace the development of the country. According to the authors the Republic future is closely connected with possibility of Bulgarian society economic growth, which ought to be fast, otherwise ‘the country of roses’ will become the 1-st country in the world that will be destroyed completely and wiped off the face of the earth without any war conflict but with the help of economic restrictions and certain mechanisms used deliberately.